How Copepods Can Eat Toxins Without Getting Sick: Gut Bacteria Help Zooplankton to Feed in Cyanobacteria Blooms - Gorokhova, Elena; El-Shehawy, Rehab; Lehtiniemi, Maiju; Garbaras, Andrius (Frontiers in Microbiology, 2021)
Toxin-producing cyanobacteria can be harmful to aquatic biota, although some grazers utilize them with often beneficial effects on their growth and reproduction. It is commonly assumed that gut microbiota facilitates host adaptation to the diet; however, the evidence for adaptation mechanisms is scarce. Here, we investigated the abundance of mlrA genes in the gut of the Baltic copepods Acartia bifilosa and Eurytemora affinis during cyanobacteria bloom season (August) and outside it (February). The mlrA genes are unique to microcystin and nodularin degraders, thus indicating the capacity to break down these toxins by the microbiota. The mlrA genes were expressed in the copepod gut year-round, being >10-fold higher in the summer than in the winter populations. Moreover, they were significantly more abundant in Eurytemora than Acartia. To understand the ecological implications of this variability, we conducted feeding experiments using summer- and winter-collected copepods to examine if/how the mlrA abundance in the microbiota affect: (1) uptake of toxic Nodularia spumigena, (2) uptake of a non-toxic algal food offered in mixtures with N. spumigena, and (3) concomitant growth potential in the copepods. The findings provide empirical evidence that the occurrence of mlrA genes in the copepod microbiome facilitates nutrient uptake and growth when feeding on phytoplankton mixtures containing nodularin-producing cyanobacteria; thus, providing an adaptation mechanism to the cyanobacteria blooms.